Factors Related to Cafe Worker’s Lung Capacity in Pontianak, Indonesia - Sunarsieh, Sunarsieh; Repelita, Felina; Akhmadi, Zainal (Kesmas, 2022)
Exposure to cigarette smoke in public places affects the human population lung capacity. Cafe workers are a population susceptible to cigarette smoke exposure. This study aimed to analyze the risk factors associated with the lung capacity of cafe workers. This study used an observational method with a cross-sectional approach. The sample was composed of 74 participants. Data collection was carried out by interviewing and observing respondents. Exposure to inhaled smoke was measured using interviews and a spirometer checking lung capacity. The Chi-square test was used to determine the relationship between risk factors and lung capacity. The results showed a significant relationship between age (p-value = 0.006) and the lung capacity of cafe workers. The older person had, the greater the risk of decreased lung function. There was a significant relationship between cigarette smoke exposure, age, and the lung capacity of cafe workers. The intervention needs to be done to make a preventive measure by establishing non-smoking area regulations in public spaces and monitoring the workplace environment.